Possible Involvement of the Drug Transporters P Glycoprotein and Multidrug Resistance-Associated Protein Mrp2 in Disposition of Azithromycin - Sugie, Masami (American Society for Microbiology, 2004)
P glycoprotein and multidrug resistance-associated protein 2 (Mrp2), ATP-dependent membrane transporters, exist in a variety of normal tissues and play important roles in the disposition of various drugs. The present study seeks to clarify the contribution of P glycoprotein and/or Mrp2 to the disposition of azithromycin in rats. The disappearance of azithromycin from plasma after intravenous administration was significantly delayed in rats treated with intravenous injection of cyclosporine, a P-glycoprotein inhibitor, but was normal in rats pretreated with intraperitoneal injection erythromycin, a CYP3A4 inhibitor. When rats received an infusion of azithromycin, cyclosporine and probenecid, a validated Mrp2 inhibitor, significantly decreased the steady-state biliary clearance of azithromycin to 5 and 40% of the corresponding control values, respectively. However, both inhibitors did not alter the renal clearance of azithromycin, suggesting the lack of renal tubular secretion of azithromycin. Tissue distribution experiments showed that azithromycin is distributed largely into the liver, kidney, and lung, whereas both inhibitors did not alter the tissue-to-plasma concentration ratio of azithromycin. Significant reduction in the biliary excretion of azithromycin was observed in Eisai hyperbilirubinemic rats, which have a hereditary deficiency in Mrp2. An in situ closed-loop experiment showed that azithromycin was excreted from the blood into the gut lumen, and the intestinal clearance of azithromycin was significantly decreased by the presence of cyclosporine in the loop. These results suggest that azithromycin is a substrate for both P glycoprotein and Mrp2 and that the biliary and intestinal excretion of azithromycin is mediated via these two drug transporters.